(3COhGJ Jbjje GdCOGA GdeGdj aj GdHfhc GdJLGQjI s - (3Hf LOh(B, (3CejfIs ((3GdLRGFQs (3OGQ GdHGMK ddWHGYI hGdfTQ hGdJhRjYs, 2023)
(3jgOa gPG GdcJGH Edi TQM eaghe GdCOGA GdeGdj hYedjI Jbjjeg, hcPGdc Edi eGgjI GdJMdjd GdeGdj hCHQR COhGJg hCSGdjHg,hHGdCNU CSdhH GdfSH GdeGdjI hJHjGf CgejJg aj JMdjd GdHjGfGJ GdeGdjI hJaSjQ OdGdJgG(B.(3ceG jgOa gPG GdcJGH Edi GdJWQb dCge GdeDTQGJ GdeGdjI hGdfSH GdJj JfOQL JMJgG hGdJj JSJNOe aj YedjI Jbjje GdCOGA GdeGdj aj GdHfhc GdJLGQjI HGdEVGaI Edi JhVjM GdYdGbI Hjf eNJda gPg GdeDTQGJ GdeGdjI hGdJj JfOQL JMJgG eNJda GdfSH GdeGdjI(B.s
Keywords: (3GdHfhcs; (3Jbjje GdCOGAs